PROTON PUMP INHIBITORS AND THE INCREASED RISK OF CLOSTRIDIUM DIFFICILE INFECTIONS: A CASE-CONTROL STUDY - DR FAHAD AS AL-EIDAN, BSc, PhD (International Journal of Pharma and Bio Sciences, 2013)
The increasing incidence of Clostridium difficile infections (CDIs) is of growing concern to physicians and health-care providers worldwide. The use of antimicrobials and proton pump inhibitors (PPIs) have been implicated as risk factors in the development of these infections. Objectives: The aim of this study is to evaluate the association between PPIs and CDI among Saudi hospitalized patients in a tertiary care teaching hospital. Methods: A one-year retrospective case-control study was conducted from January to December 2011 in King Abdulaziz Medical City, Riyadh. Ninety eight CDI cases were identified and matched with a similar control number for age, sex, and relevant hospital unit. The two groups were compared and analyzed using logistic regression models to determine factors associated with incidence of CDIs. Results: In the two comparison groups, mean age, gender ratio, co-morbid diseases, history of surgery, other medications received, including antimicrobials, did not differ, but use of PPIs was significantly higher among CDI cases (P<0.0001). The incidence of CDI was 10.8 cases/100 patient-years. In multivariate logistic regression model, use of PPIs (odds ratio [OR] 19.12, a 95% confidence interval [CI] 9.25-39.52) and length of hospital stay (OR1.20, 95% CI1.11-1.31) were the only variables significantly associated with the risk of CDI. Conclusion: Longer hospitalized patients exposed to PPIs showed significant association with the development of Clostridium difficile infections.